2011
DOI: 10.1002/jwmg.63
|View full text |Cite
|
Sign up to set email alerts
|

Using multiple methods to assess detection probabilities of forest‐floor wildlife

Abstract: Many previous comparisons of multiple sampling methods have assumed that detection probabilities for each method are either constant or equal to one. We used 4 sampling methods to estimate detection probabilities for forest-floor dwelling amphibians, reptiles, and small mammals. We investigated associations between seasonality and precipitation on species detection and explored sample design tradeoffs for future studies. Although we captured 25 species, we could reliably detect (detection probability >0.15) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Smith, unpubl. data), and is consistent with other studies of P. cinereus activity in northern parts of its range (e.g., DeGraaf and Yamasaki, 2002;Leclair et al, 2008;Otto and Roloff, 2011). Nagel (1977) showed that P. cinereus populations in the southernmost part of the species' range are active for most of the year with only a short inactive period during the summer, suggesting a single extended activity period rather than a bimodal pattern each year.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Smith, unpubl. data), and is consistent with other studies of P. cinereus activity in northern parts of its range (e.g., DeGraaf and Yamasaki, 2002;Leclair et al, 2008;Otto and Roloff, 2011). Nagel (1977) showed that P. cinereus populations in the southernmost part of the species' range are active for most of the year with only a short inactive period during the summer, suggesting a single extended activity period rather than a bimodal pattern each year.…”
Section: Discussionsupporting
confidence: 90%
“…The effective use of terrestrial salamanders as ecological indicators depends on whether or not the data being collected is accurate and repeatable. Some of the more common methods of monitoring terrestrial salamanders have been the use of transect counts, quadrat searches, funnel traps, pitfall traps, searches of natural cover objects, and searches of artificial cover objects (Bailey et al, 2004;Strain et al, 2009;Otto and Roloff, 2011).…”
Section: Inroductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of herpetofauna can vary with large‐scale habitat characteristics (e.g., aspect and elevation), small‐scale habitat characteristics (e.g., nearby downed woody debris), environmental conditions (e.g., rain and temperature), and species (MacKenzie et al. , Otto and Roloff ). N ‐mixture models estimate population sizes from count surveys of unmarked animals while simultaneously accounting for imperfect detection (Royle ).…”
Section: Methodsmentioning
confidence: 99%
“…We used spatial, as opposed to temporal, replication for sampling salamanders because it minimized the number of repeated visits to each site and reduced travel between sites. Furthermore, previous work shows that temporally replicated cover object searches often violate the “closure” assumption of the state-space models we used for analysis [30], [33]. Each transect was surveyed once unless it was selected with replacement, in which case it was surveyed again 12–16 days later.…”
Section: Methodsmentioning
confidence: 99%